Endocrine disrupting chemicals in personal care products: knowledge, attitudes, and perceptions among pregnant women in South Africa - Paul, Lissa (Department of Public Health and Family Medicine, 2025)
The widespread and frequent use of cosmetics has led to increased exposure to harmful chemicals including endocrine-disrupting chemicals (EDCs), which are known to interfere with the endocrine system. Exposure to EDCs is particularly concerning during pregnancy with research indicating potential health effects such as gestational diabetes, birth defects, neurological disorders, and endocrine cancers. While high-income countries have started to take steps to raise public awareness, as well as develop and enforce regulation of EDCs in cosmetics, South Africa lags in this regard. Research shows that there is a need to ensure that risk communication measures of hazardous chemicals in products are effective and comprehended as intended by consumers. This will support informed product choices, thereby promoting consumer safety and well-being. However, the extent to which pregnant women are aware of harmful chemicals in their cosmetics and how they perceive their health risks remain unexplored in South Africa. This study investigated knowledge, attitudes, and perceptions regarding EDCs in cosmetics among 102 pregnant women attending antenatal healthcare visits in Cape Town, South Africa. The research protocol (Part A) provides an overview of the widespread use of cosmetics, cosmetic regulation in South Africa, common EDCs found in cosmetics, their characteristics, and exposure routes. The justification for the research was grounded on the potential health risks associated with these chemicals, especially during windows of vulnerability such as pregnancy. Furthermore, the protocol underscored the existing gaps in knowledge and awareness concerning EDCs among women globally and justified the need for similar research in South Africa. A mixed-method cross-sectional study design was used as it allowed for collecting both quantitative and qualitative variables at a single point in time. Pregnant women aged 18 years and above, who could speak English, IsiXhosa, or Afrikaans were included in the study. The data collection tools, face-to-face questionnaires, were specified, along with a discussion on their development and adaptation to suit the research context. The questionnaire was piloted to enhance its validity and reliability and collected information on demographic details, reasons for PCP use, knowledge of EDCs effects on health, identification of EDCs on cosmetic labels, attitudes toward EDCs risk, and perceptions of EDC exposure risk. The informed consent process for participants was explained, prioritizing iv transparency and participant autonomy, while confidentiality and data protection measures were clearly outlined to uphold the ethical integrity of the research. The journal-ready manuscript (part B) presents the South African case study research findings on pregnant women's knowledge of EDCs and their attitudes and perceptions of EDC risks. To determine if the same EDCs commonly reported in literature from high-income countries are also available in cosmetics commonly used in South Africa, a label analysis was conducted on products sampled from common shops. A few images of cosmetics captured during this survey were used to evaluate if pregnant women can identify any EDCs on these labels. The study found that no participant could identify EDCs on cosmetic labels. Our study participants generally did not possess a culture of reading labels before buying their products. Instead, factors such as the scent and product price took precedence. When questioned about their reluctance to read labels, most participants expressed unawareness of their responsibility to scrutinize cosmetics before purchasing them. Additionally, participants did not perceive EDCs as a substantial threat to their health or foetuses. While some women demonstrated awareness of health effects such as eczema and allergies, participants did not perceive these conditions as severe or attributable to EDC exposure. There was a notable lack of comprehensive understanding regarding how chemicals in cosmetics enter their bodies through various exposure routes, their potential transfer to the foetus in utero, concentration in breast milk, and their impact on future generations. Endocrine-related disorders such as diabetes were least associated with EDC exposure. Despite the notable gaps in awareness, women showed an interest in enhancing their understanding of these chemicals through accessible communication channels, including social media and antenatal care clinics. This presented a unique opportunity to bridge the knowledge gap by disseminating information in a simple clear language tailored to the health literacy levels of South African pregnant women. Healthcare providers can be used as trusted sources for information dissemination. Enforcement of cosmetic legislation is imperative to mitigate EDCs risks, protect maternal and foetal health, and ensure the safety of cosmetic products in the South African market. The appendices (Part C) provide additional materials that support and help understand the study results such as questionnaires and informed consent forms.